2012
DOI: 10.3892/mmr.2012.1199
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11, an interleukin-6-like cytokine, is a promising predictor for bladder cancer prognosis

Abstract: Abstract. Numerous studies have suggested that interleukin 11 (IL-11) has roles in human gastric, prostate and bone cancer and endometrial carcinoma. Hence, we evaluated the expression of IL-11 in bladder cancer and the correlation of IL-11 levels and clinico pathological features. The expression of IL-11 in primary human bladder cell culture, human bladder cancer cell lines, transitional cell carcinoma (TCC) and non-cancerous bladder tissues (NATs) were analyzed by western blotting. Enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…It is known that IL‐11 is related to the activation of osteoclasts and bone resorption resulting from tumors . The relationship of IL‐11 to tumor progression and metastasis has been described in other cancers, such as bladder cancer and renal carcinoma . Likewise, PTHrP expressed in OSCCs and other malignant tumors seems to stimulate the activity of osteoclasts, acting both in osteoclastic and osteoblastic cells; moreover, it is related to increased tumor cell proliferation, survival, adhesion, migration and invasion, and is considered an indicator of the prognosis .…”
Section: Discussionsupporting
confidence: 92%
“…It is known that IL‐11 is related to the activation of osteoclasts and bone resorption resulting from tumors . The relationship of IL‐11 to tumor progression and metastasis has been described in other cancers, such as bladder cancer and renal carcinoma . Likewise, PTHrP expressed in OSCCs and other malignant tumors seems to stimulate the activity of osteoclasts, acting both in osteoclastic and osteoblastic cells; moreover, it is related to increased tumor cell proliferation, survival, adhesion, migration and invasion, and is considered an indicator of the prognosis .…”
Section: Discussionsupporting
confidence: 92%
“…Similar downregulation of IL1B also challenging the report of Kashyap et al (2009). Wu et al (2013) has revealed association of IL11 with cancer grade and stage in bladder cancer and also suggested reduced level of IL11 may play an important role in progression of transitional cell carcinoma indicating that IL11 could be a promising predictor of cancer prognosis.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, bladder cancer is the second most common cause of mortality among genitourinary tumors, with ~72,570 new cases and 15,210 deaths occurring in males and females in 2013 ( 1 3 ). Transitional cell carcinoma (TCC) accounts for ~90% of cases of bladder cancer, whereas squamous cell carcinoma accounts for ~5% and adenocarcinomas ~1–2% of cases ( 4 ). At presentation, ~70% of cases of bladder cancer are non-muscle invasive (stages Tis, Ta and T1) which is typically low grade, multifocal, superficial and papillary, and 30% are muscle invasive (stages T2, T3 and T4), according to the TNM staging system ( 3 ).…”
Section: Introductionmentioning
confidence: 99%